Pengembangan Produk Branding Sebagai Penguatan Dalam Pemasaran Rumah Produksi Jamur Pada Paimo Farm - Dewi Puspa Arum; Siti Nurhaliza; Betaria Novila Ananda Putri; Fatima Azrina Pramesthi; Dini Hiqmatul Hayati; Muhammad Handito Perwira Negara; Muhammad Faiz Harby (Jurnal Informasi Pengabdian Masyarakat, 2023)
MSMEs play an important role in economic growth which has a direct impact on regional economic development. In the Ngadirejo Village, Kepanjenkidul District, Blitar City, there is an UMKM "Paimo Farm" which is an oyster mushroom production house. A mushroom production house is a place for cultivating mass-produced mushrooms. The MSME branding products that are applied are also classified as standard as product-related information, causing the number of product sales to be less known to consumers. This activity is intended so that the "Paimo Farm" MSME can develop into a bigger business and can be widely known outside the city through product branding. Data collection methods used were interviews and direct observation by collecting primary and secondary data. The ultimate goal of this community service activity is to improve entrepreneurship skills through various stages which include outreach and assistance to MSMEs related to digital marketing, logo design creation, product packaging optimization coaching and product photo coaching as an effort in developing the "Paimo Farm" MSME business.